Extraction of mineral acids with neutral oxygen containing compounds from mixed nitric-chloride solutions - G. V. Kostikova; O. A. Kutepova; A. M. Reznik; A. Yu. Tsivadze; Yu. S. Krylov; E. V. Salnikova (Тонкие химические технологии, 2013)
Data on a systematic research of the extraction of nitric and chloride acids from mixed nitric-chloride solutions with neutral oxygen containing compounds – triisoamylphosphate and isoamyldyalkyl (C7–C9) phosphine oxide are presented. The composition of the extracted compounds is determined, the isotherms of the extraction of acids for solutions with different salt composition are obtained. It is shown that from the nitric-chloride mixed solutions of different composition, when used as extractants neutral oxygen containing compounds, in organic phase goes mainly nitric acid.